CXXC finger protein 1 is critical for T-cell intrathymic development through regulating H3K4 trimethylation - Cao, Wenqiang; Guo, Jing; Wen, Xiaofeng; Miao, Li; Lin, Feng; Xu, Guanxin; Ma, Ruoyu; Yin, Shengxia; Hui, Zhaoyuan; Chen, Tingting; Guo, Shixin; Chen, Wei; et al. (Nature communications, 2016)
T-cell development in the thymus is largely controlled by an epigenetic program, involving in both DNA methylation and histone modifications. Previous studies have identified Cxxc1 as a regulator of both cytosine methylation and histone 3 lysine 4 trimethylation (H3K4me3). However, it is unknown whether Cxxc1 plays a role in thymocyte development. Here we show that T-cell development in the thymus is severely impaired in Cxxc1 -deficient mice. Furthermore, we identify genome-wide Cxxc1-binding sites and H3K4me3 modification sites in wild-type and Cxxc1 -deficient thymocytes. Our results demonstrate that Cxxc1 directly controls the expression of key genes important for thymocyte survival such as RORγt and for T-cell receptor signalling including Zap70 and CD8, through maintaining the appropriate H3K4me3 on their promoters. Importantly, we show that RORγt, a direct target of Cxxc1, can rescue the survival defects in Cxxc1 -deficient thymocytes. Our data strongly support a critical role of Cxxc1 in thymocyte development. T cell development has been a classical model for understanding cell fate regulation by epigenetics. Here the authors show that Cxxc1 controls thymocyte development mainly through regulating several key genes, such as Rorc , Zap70 and Cd8 , which requires its H3K4me3 but not DNA methylation function.